1992
DOI: 10.1111/j.1365-2125.1992.tb04131.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of cimetidine to reduce dapsone‐dependent methaemoglobinaemia in dermatitis herpetiformis patients.

Abstract: 1. We have attempted to reduce dapsone‐dependent methaemoglobinaemia formation in six dermatitis herpetiformis patients stabilised on dapsone by the co‐administration of cimetidine. 2. In comparison with control, i.e. dapsone alone, methaemoglobinaemia due to dapsone fell by 27.3 +/‐ 6.7% and 26.6 +/‐ 5.6% the first and second weeks after commencement of cimetidine administration. The normally cyanotic appearance of the patient on the highest dose of dapsone (350 mg day‐ 1), underwent marked improvement. 3. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
51
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(54 citation statements)
references
References 28 publications
0
51
1
2
Order By: Relevance
“…Cimetidine, a histamine H 2 receptor antagonist, can reduce the N-hydroxylation of dapsone [31] . This reduction was demonstrated to result in more than a 25% decrease in methemoglobinemia in patients who received dapsone for the treatment of dermatitis herpetiformis [32] . The coadministration of cimetidine can be considered in selected patients, especially when high doses of dapsone are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Cimetidine, a histamine H 2 receptor antagonist, can reduce the N-hydroxylation of dapsone [31] . This reduction was demonstrated to result in more than a 25% decrease in methemoglobinemia in patients who received dapsone for the treatment of dermatitis herpetiformis [32] . The coadministration of cimetidine can be considered in selected patients, especially when high doses of dapsone are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Various hepatic enzymes, such as the cytochrome P450-dependent monooxygenases, cyclooxygenases, and PRXs, have been shown to be active in SMX and DDS metabolism (Cribb et al, 1990;Mitra et al, 1995;Goebel et al, 1999;Winter et al, 2000). Although survival of reactive metabolites during transit from liver to skin has not been demonstrated, evidence suggests the presence of the hydroxylamine metabolites of these drugs in plasma and urine after therapeutic doses (Coleman et al, 1992;Mitra et al, 1995;Winter et al, 2000). It is noteworthy that the concentration of SMX in skin blisters of subjects receiving this drug achieves 82% of those observed in plasma (Krolicki, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on vitamin C doses that are >1 m M (attainable by intravenous administration) have found methemoglobinemia reduction; however, oral administration cannot exceed 200 µ M because of the gastrointestinal absorption [28,29,30]. Studies on the cytochrome P450 inhibitor cimetidine in rats and small studies on humans have found that concurrent administration reduces levels of methemoglobinemia [31,32]. In humans, this reduction was demonstrated with a dose of cimetidine 8-hourly, with 800 mg/h prior to the dapsone dose and 2 subsequent doses of 400 mg each, administered for 3 weeks (but not longer than 12 weeks) [33].…”
Section: Discussionmentioning
confidence: 99%